Pengembangan model kelembagaan konservasi sapi Madura - Suprih Bambang Siswijono; V. M. Ani Nurgiartiningsih; Hermanto Hermanto (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
Long-term goals of this research were to increase production and maintain purity of Madura cattle as one of Indonesian native cattle. The specific objectives of this study was to develop an institutional model of conservation of Madura cattle as a base for improving productivity and empowerment of Madura cattle farmer. The research was conducted by survey method. Data collection were done by the technique of interview, observation participation and Foccus Group Discussion (FGD) and the Delphi technique. The instruments for data collection were questionnaire and interview guidelines. The results showed that the highest increament of cattle population was found in Bangkalan district. Most of the households managed 2-3 cattle which belong to their own, but there were still 32.50 percent of households managed share cattle.  Mating system using artificial insemination of excotic breed frozen semen has been commonly used among the farmers. Reproductive performance of Madura cattle was good indicated by service per conseption (S/C) of 1.5 and calving interval (CI) of 18 months. With regards to perception, farmers tended to agree with cross-breeding between Madura cattle with semen of exotic breed. This was mainly due to economic aspect in which crossbred cattle was more expensive than local cattle. Determination of Sapudi Island as a breeding centre of Madura cattle showed as an institutional changes of Madura cattle conservation. The development of institutional model of Madura cattle conservation should consider the economic, technical and social aspects. It coul be suggested that the guidance and supervision of the farmers need to be carried out continuously as an effort to preserve the purity of Madura cattle. Economic incentives as a reward for farmers who rear Madura cattle should be a major consideration in the development of an institutional model of Madura cattle conservation. In addition, madurese community must be involved in the development of institutional model for Madura cattle conservation.   Keywords: Institution, conservation, genetic resources, Madura cattle